Layered high-entropy oxide sodium ion battery positive electrode material
By adopting a layered structure in the positive electrode material of sodium ion battery, including a high-entropy oxide core, a gradual change potential outer layer and a phase change stress buffer layer, the performance bottleneck of existing materials under cyclic and high-magnification conditions is achieved. Higher electrochemical stability, rate performance and cycle life.
Patent Information
- Application Number
- CN202411555807.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The existing sodium ion battery positive electrode materials face problems such as insufficient electrochemical stability, low rate performance, and rapid capacity attenuation under long-term recycling and high-rate charging and discharge conditions, which are mainly due to the lattice structure caused by the embedding and deintercalation of sodium ions. Change and stress accumulation.
The positive electrode material of the layered high-entropy oxide sodium ion battery is used, including the high-entropy oxide core, a gradual change potential outer layer and a phase change stress buffer layer. The gradual change potential outer layer consists of multiple layers of oxides with different sodium content, providing a gradual change of electrochemical environment to help homogenize and deintercalate sodium ions. The phase change stress buffer layer is composed of silicates for absorbing and releasing mechanical stresses caused by the phase change.
Through this structural design, the electrochemical stability and rate performance of the material are significantly improved, the cycle life of the battery is extended, and the energy density and overall performance are improved.
Smart Images

Figure CN119419249A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery positive electrode materials, and in particular relates to a layered high entropy oxide sodium ion battery positive electrode material. Background Art
[0002] As an alternative technology to lithium-ion batteries, sodium-ion batteries have received widespread attention in recent years. This is because sodium resources are widely distributed on the earth and have abundant reserves, which is more cost-effective and sustainable than lithium resources. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. The core is the reversible insertion / deinsertion process of sodium ions between the positive and negative electrodes. However, the larger radius of sodium ions means that their migration speed and embeddability in materials are usually not as good as lithium ions, which places more stringent requirements on positive electrode materials.
[0003] The performance of cathode materials directly affects the energy density, cycle life and safety performance of sodium-ion batteries. Therefore, the research and improvement of cathode materials is the key to promoting the development of sodium-ion battery technology. Traditional cathode materials for sodium-ion batteries, such as layered oxides, have certain advantages in terms of cost and resource availability, but they often face problems such as insufficient electrochemical stability, low rate performance, and rapid capacity decay under long-term cyclic use and high-rate charge and discharge conditions. These problems are mainly attributed to the lattice structure changes and stress accumulation caused by the insertion and deinsertion of sodium ions, which lead to uneven electrochemical reactions inside the electrode materials.
[0004] In addition, since the insertion / deinsertion of sodium ions will cause the expansion and contraction of the lattice volume, this repeated volume change can easily induce mechanical stress and phase change inside the material, thereby accelerating the structural degradation and electrochemical performance decline of the material. This mechanical damage to the material not only reduces the life of the battery, but may also pose a safety hazard.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a layered high entropy oxide sodium ion battery positive electrode material.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention is to provide a layered high entropy oxide sodium ion battery positive electrode material, comprising a high entropy oxide core, a gradient chemical potential outer layer, and a phase change stress buffer layer, wherein the phase change stress buffer layer is arranged between the high entropy oxide core and the gradient chemical potential outer layer, and the phase change stress buffer layer is composed of silicate, the gradient chemical potential outer layer is composed of multiple layers of oxides with different sodium contents, and the high entropy oxide core is formed by doping multiple transition metal elements in an equiatomic ratio.
[0009] Single-phase solid solution. The outer layer with a gradient chemical potential can provide a gradually changing electrochemical environment through the design of multiple oxide layers with different sodium contents. This structural design helps to uniformly embed and de-embedding the sodium ions, reduce potential fluctuations and local stress accumulation, and thus improve the electrochemical stability and rate performance of the material.
[0010] Secondly, by being placed between the high entropy oxide core and the gradient chemical potential outer layer, it can effectively absorb and release stress when sodium ions are inserted and removed to cause volume changes. This design not only prevents structural damage to the material caused by mechanical stress, but also avoids rapid performance degradation, significantly improving the cycle life of the battery.
[0011] Finally, by combining the gradient chemical potential outer layer with the phase change stress buffer layer, the present invention not only solves the performance bottleneck of traditional materials under cycling and high rate conditions, but also improves the overall electrochemical performance and energy density of the battery.
[0012] Optionally, the high entropy oxide core includes Fe, Co, Ni, Sn and Ti, Fe, Co, Ni, Sn and Ti are doped in an atomic ratio of 1:1:1:1:1, and the grain size of the high entropy oxide core is 100nm to 500nm.
[0013] Optionally, Fe, Co, Ni, Sn and Ti are respectively Fe2O3, Co3O4, NiO, MnO2 and TiO2 with a purity of more than 99.9%.
[0014] Optionally, the graded chemical potential outer layer is deposited layer by layer by chemical vapor deposition technology, and the thickness of each oxide layer during the coating process is 10-50nm.
[0015] Optionally, the thickness of the phase change stress buffer layer is 0.1-5 μm.
[0016] A layered high entropy oxide sodium ion battery positive electrode material, the preparation method comprising the following steps:
[0017] Step 1: Fe2O3, Co3O4, NiO, MnO2 and TiO2 are mixed in an equiatomic ratio to obtain a precursor powder, and then the precursor powder is mixed evenly with anhydrous ethanol to obtain product ①;
[0018] Step 2: Use a high-energy ball mill to ball mill the product ①, the ball milling conditions are set to 200-400 rpm / min, and the ball milling time is 2-5 hours. After the ball milling is completed, precursor powders of various transition metals are obtained;
[0019] Step 3: Pre-sintering the precursor powders of various transition metals at a temperature of 700°C for 4 hours, and then sintering at a high temperature of 850°C-950°C for 8-12 hours to form a high entropy oxide core;
[0020] Step 4: uniformly coating the sodium silicate sol on the surface of the high entropy oxide core, drying the coated material at 70°C, and then calcining it at a temperature range of 300°C-500°C for 1-3h, and forming a phase change stress buffer layer on the surface of the high entropy oxide core after calcination;
[0021] Step 5: using chemical vapor deposition technology to deposit oxide layers with different sodium contents on the surface of the phase change stress buffer layer to prepare a gradient chemical potential outer layer;
[0022] Step 6: Grind and sieve the prepared preliminary positive electrode material to obtain a positive electrode material with a particle size of 2-10 μm.
[0023] Optionally, the steps of depositing oxide layers with different sodium contents on the surface of the phase change stress buffer layer using chemical vapor deposition technology are:
[0024] Step 5.1: placing the high entropy oxide core in a CVD reaction chamber, then introducing sodium precursor gas and argon gas into the CVD reaction chamber, reacting at a reaction temperature of 300° C. to 500° C. for 1 to 3 hours;
[0025] Step 5.2: After all layers are deposited, keep the argon flow, and then anneal at 500 °C for 2 h.
[0026] Optionally, in step 1, the mass ratio of the precursor powder to anhydrous ethanol is 1:(2-5).
[0027] Optionally, the gradient chemical potential outer layer has an inner layer, an intermediate layer, and an outer layer with a gradually decreasing sodium content from high sodium content, wherein the sodium precursor gas concentration is set to 0.5M, the argon flow rate is 150sccm, and the deposition time is 1h when depositing the inner layer, and the sodium precursor gas concentration is adjusted to 0.2M when depositing the intermediate layer, the argon flow rate is maintained at 150sccm, and the deposition time is 45min. When depositing the outer layer, the sodium precursor gas concentration is adjusted to 0.05M, the argon flow rate is 150sccm, and the deposition time is 30min. By reducing the sodium content layer by layer, a sodium ion concentration gradient is formed from the inner layer to the outer layer. This design helps sodium ions to achieve smoother embedding and de-embedding during the charge and discharge process, reduces mutations in the ion migration path, and reduces local stress and potential fluctuations caused by rapid embedding or de-embedding of sodium ions. Secondly, the different regulation of the sodium content in each layer can form a gradient chemical potential between the layers of materials, thereby effectively alleviating the stress concentration and phase change risks of sodium ions during the embedding and de-embedding process, preventing the structural collapse and performance degradation of the electrode material, and significantly improving the electrochemical stability of the electrode material. More specifically, the inner layer with a high sodium content can quickly provide sodium ions, while the outer layer with a low sodium content can act as a buffer to control the release rate of sodium ions. Through this layered design, the battery can respond quickly under high-rate charge and discharge conditions while maintaining high capacity and efficiency.
[0028] Optionally, the chemical formula of the prepared positive electrode material is Na x (Fe y Co y Ni y Mn y Ti y )O2, where 0≤x≤1, 0.1≤y≤0.31.
[0029] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0030] By combining a gradient chemical potential outer layer with a phase change stress buffer layer, the present invention achieves multiple performance optimizations of the positive electrode material of a sodium ion battery. The gradient chemical potential outer layer is composed of oxide layers with different sodium contents, forming an electrochemical potential gradient, balancing the embedding and de-embedding of sodium ions during the charge and discharge process, reducing potential fluctuations, and improving electrochemical stability and rate performance. The phase change stress buffer layer utilizes the flexibility of silicate materials to alleviate the mechanical stress caused by volume change and phase change, and prevent structural damage and performance degradation. The synergistic effect of the two significantly extends the cycle life of the battery, improves energy density and overall performance, and is suitable for a variety of energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1This is a SEM image of the positive electrode material of the sodium ion battery in Example 1 of the present invention, wherein the central part of the image shows a dense granular structure, which is the high entropy oxide core, characterized by a complex microstructure formed by the uniform distribution of multiple transition metal elements, reflecting the high mixed entropy characteristics. Surrounding the high entropy oxide core is a gradient chemical potential outer layer, the texture of this layer gradually changes, showing the difference in sodium content in different regions, forming a chemical potential gradient, and optimizing the embedding and diffusion path of sodium ions. The outermost layer is a phase change stress buffer layer, which is used to effectively absorb and release stress during the charge and discharge process, and prevent the volume change caused by the phase change from damaging the inner layer material, thereby improving the cycle stability and life of the material. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] See also Figure 1As shown, an embodiment of the present invention discloses a layered high entropy oxide sodium ion battery positive electrode material, comprising a high entropy oxide core, a gradient chemical potential outer layer, and a phase change stress buffer layer, wherein the phase change stress buffer layer is arranged between the high entropy oxide core and the gradient chemical potential outer layer, and the phase change stress buffer layer is composed of silicate, the gradient chemical potential outer layer is composed of multiple layers of oxides with different sodium contents, and the high entropy oxide core is a single-phase solid solution formed by doping multiple transition metal elements in equiatomic ratios.
[0038] In this embodiment, the high entropy oxide core includes Fe, Co, Ni, Sn and Ti, and Fe, Co, Ni, Sn and Ti are doped in an atomic ratio of 1:1:1:1:1. The grain size of the high entropy oxide core is 100nm-500nm.
[0039] In this embodiment, Fe, Co, Ni, Sn and Ti are respectively Fe2O3, Co3O4, NiO, MnO2 and TiO2 with a purity of more than 99.9%.
[0040] In this embodiment, the graded chemical potential outer layer is deposited layer by layer by chemical vapor deposition technology, and the thickness of each oxide layer during the coating process is 10-50 nm.
[0041] In this embodiment, the thickness of the phase change stress buffer layer is 0.1-5 μm.
[0042] A layered high entropy oxide sodium ion battery positive electrode material, the preparation method of which comprises the following steps:
[0043] Step 1: Fe2O3, Co3O4, NiO, MnO2 and TiO2 are mixed in an equiatomic ratio to obtain a precursor powder, and then the precursor powder is mixed evenly with anhydrous ethanol to obtain product ①;
[0044] Step 2: Use a high-energy ball mill to ball mill the product ①, the ball milling conditions are set to 200-400 rpm / min, and the ball milling time is 2-5 hours. After the ball milling is completed, precursor powders of various transition metals are obtained;
[0045] Step 3: Pre-sintering the precursor powders of various transition metals at a temperature of 700°C for 4 hours, and then sintering at a high temperature of 850°C-950°C for 8-12 hours to form a high entropy oxide core;
[0046] Step 4: uniformly coating the sodium silicate sol on the surface of the high entropy oxide core, drying the coated material at 70°C, and then calcining it at a temperature range of 300°C-500°C for 1-3h, and forming a phase change stress buffer layer on the surface of the high entropy oxide core after calcination;
[0047] Step 5: using chemical vapor deposition technology to deposit oxide layers with different sodium contents on the surface of the phase change stress buffer layer to prepare a gradient chemical potential outer layer;
[0048] Step 6: Grind and sieve the prepared preliminary positive electrode material to obtain a positive electrode material with a particle size of 2-10 μm.
[0049] In this embodiment, the steps of depositing oxide layers with different sodium contents on the surface of the phase change stress buffer layer using chemical vapor deposition technology are as follows:
[0050] Step 5.1: placing the high entropy oxide core in a CVD reaction chamber, then introducing sodium precursor gas and argon gas into the CVD reaction chamber, reacting at a reaction temperature of 300° C. to 500° C. for 1 to 3 hours;
[0051] Step 5.2: After all layers are deposited, keep the argon flow, and then anneal at 500 °C for 2 h.
[0052] In this embodiment, the mass ratio of the precursor powder to anhydrous ethanol in step 1 is 1:(2-5).
[0053] In this embodiment, the gradient chemical potential outer layer has an inner layer, an intermediate layer, and an outer layer with a gradually decreasing sodium content from a high sodium content. When depositing the inner layer, the sodium precursor gas concentration is set to 0.5M, the argon gas flow rate is 150sccm, and the deposition time is 1h. When depositing the intermediate layer, the sodium precursor gas concentration is adjusted to 0.2M, the argon gas flow rate is maintained at 150sccm, and the deposition time is 45min. When depositing the outer layer, the sodium precursor gas concentration is adjusted to 0.05M, the argon gas flow rate is 150sccm, and the deposition time is 30min.
[0054] In this embodiment, the chemical formula of the prepared positive electrode material is Na x (Fe y Co y Ni y Mn y Ti y )O2, where 0≤x≤1, 0.1≤y≤0.31.
[0055] The present invention will now be further described in detail with reference to embodiments.
[0056] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.
[0057] Example 1: A method for preparing a layered high entropy oxide sodium ion battery positive electrode material is as follows:
[0058] Weigh Fe2O3, Co3O4, NiO, MnO2 and TiO2 with a purity of more than 99.9% in an equiatomic ratio of 1:1:1:1:1 as raw materials for the high entropy oxide core. Next, mix these precursor powders with anhydrous ethanol in a mass ratio of 1:3 to ensure uniform dispersion;
[0059] The mixed precursor powders were ball-milled using a high-energy ball mill, with the rotation speed set at 300 rpm and the ball-milling time set at 4 hours to obtain uniform transition metal oxide precursor powders;
[0060] The ball-milled precursor powder was pre-sintered at 700°C for 4 hours and then sintered at 900°C for 10 hours to form a high-entropy oxide core with a grain size of 500 nm.
[0061] Sodium silicate sol was used to evenly coat the surface of the high entropy oxide core. The coated material was dried at 70°C and then calcined at 400°C for 2 hours to form a phase change stress buffer layer with a thickness of 2 microns;
[0062] The sodium oxide layer was deposited on the surface of the phase change stress buffer layer using chemical vapor deposition technology. The reaction temperature was set to 400°C, and the carrier gas (argon) flow rate was 150sccm: the inner layer sodium precursor gas concentration was 0.5M, and the deposition time was 1 hour; the middle layer sodium precursor gas concentration was 0.2M, and the deposition time was 45 minutes; the outer layer sodium precursor gas concentration was 0.05M, and the deposition time was 30 minutes;
[0063] After all the deposited layers were completed, the argon gas flow was maintained, and then the sample was annealed at 500 °C for 2 h to improve the crystallinity and interfacial bonding strength of the oxide layer;
[0064] The prepared preliminary positive electrode material was ground and sieved to obtain a positive electrode material with a particle size of 10 μm.
[0065] Embodiment 2: The differences compared with Embodiment 1 include:
[0066] Mixing ratio of precursor powder and anhydrous ethanol: Mix the precursor powder and anhydrous ethanol in a mass ratio of 1:4.
[0067] Ball milling conditions: The ball mill speed was set to 350 rpm and the ball milling time was extended to 5 hours. Sintering conditions:
[0068] The pre-sintering temperature is still 700°C and the time is 4 hours; the high-temperature sintering temperature is increased to 950°C and the sintering time is reduced to 8 hours.
[0069] Thickness of the phase change stress buffer layer: by adjusting the calcination conditions, the thickness of the buffer layer is 1 micron (calcination temperature 350° C., time 1.5 hours).
[0070] Deposition of the outer layer with graded chemical potential: the deposition temperature was reduced to 350 °C and the argon flow rate was reduced to 100 sccm.
[0071] Embodiment 3: The differences compared with Embodiment 1 include:
[0072] The high-energy ball mill used was set at a speed of 250 rpm and a ball milling time of 3 hours. The pre-sintering temperature was 700°C for 4 hours; the high-temperature sintering temperature was set at 900°C and the sintering time was extended to 12 hours.
[0073] By adjusting the calcination conditions, the thickness of the buffer layer was increased to 3 microns, and the calcination temperature was 450°C for 3 hours. Sodium fluoride was used as the sodium source during the chemical deposition process, the CVD deposition reaction temperature was increased to 450°C, and the argon gas flow rate was maintained at 150 sccm.
[0074] Comparative Example 1: The preparation of the gradient chemical potential outer layer in Examples 1-3 was omitted, and the surface of the high entropy oxide core was directly coated with sodium silicate sol after sintering to form the high entropy oxide core.
[0075] Comparative Example 2: The preparation of the gradient chemical potential outer layer in Examples 1-3 was removed, and the surface of the high entropy oxide core was directly coated with sodium silicate sol after sintering to form the high entropy oxide core.
[0076] Comparative Example 3: The gradient chemical potential outer layer and phase change stress buffer layer in Examples 1-3 are removed, and the high entropy oxide core is directly used as the positive electrode material.
[0077] Experimental example: positive electrode material experimental test
[0078] First, the positive electrode material is mixed with the conductive agent and the binder in a ratio of 70:20:10, dissolved with N-methylpyrrolidone, and stirred evenly to form a slurry. Then, the slurry is coated on the aluminum foil current collector, vacuum dried, and pressed to obtain the positive electrode sheet. The prepared positive electrode sheet, the metal sodium negative electrode sheet, the electrolyte and the separator are assembled into a button cell. Subsequently, the first discharge capacity and coulomb efficiency of the battery are tested. Then, a cycle stability test is performed to record the capacity retention rate after each cycle. Finally, a rate performance test is performed to measure the discharge capacity of the battery at different rates such as 0.1C, 1C, and 5C. The data obtained are shown in Table 1.
[0079] Table 1: Comparison table of implementation examples 1-3 and control examples 1-3
[0080]
[0081] As can be seen from Table 1, the gradient chemical potential outer layer forms a chemical potential gradient by depositing oxide layers with different sodium contents in the electrode material, thereby dynamically optimizing the diffusion path and speed of sodium ions during the charge and discharge process. This chemical potential gradient enables sodium ions to migrate along the optimal path, effectively improving the ionic conductivity of the electrode material, and enhancing the rate performance of the battery (for example, the capacity of Example 1 at 5C is 135mAh / g, while that of Control Example 1 is only 95mAh / g), while reducing the local stress and damage caused by the uneven path during the migration of sodium ions, thereby improving the capacity retention rate (for example, the capacity retention rate of Example 1 after 100 cycles is 97%, while that of Control Example 1 is 86%).
[0082] The phase change stress buffer layer is located between the high entropy oxide core and the gradient chemical potential outer layer, and is specifically used to absorb and release the mechanical stress caused by the phase change, preventing the electrode material from having micro cracks or structural failure due to volume changes during the charge and discharge process. This buffering effect significantly improves the cycle stability of the battery (for example, the capacity retention rate of Example 1 is 97%, while that of Control Example 3 is only 80%), and also indirectly improves the first discharge capacity (for example, the first discharge capacity of Example 1 is 162mAh / g, while that of Control Example 2 is only 132mAh / g), because the buffer layer reduces the structural damage during the first charge and discharge, and maintains the integrity and activity of the material.
[0083] In summary, the gradient chemical potential outer layer significantly improves the battery's rate performance and capacity retention by optimizing the diffusion path and speed of sodium ions, while the phase change stress buffer layer significantly improves the battery's cycle stability and first discharge capacity by relieving mechanical stress and preventing material damage. The synergistic effect of these two layers effectively extends the battery's service life and improves its overall performance.
[0084] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A layered high entropy oxide sodium ion battery positive electrode material, characterized in that: It includes a high entropy oxide core, a gradient chemical potential outer layer, and a phase change stress buffer layer, wherein the phase change stress buffer layer is arranged between the high entropy oxide core and the gradient chemical potential outer layer, and the phase change stress buffer layer is composed of silicate, the gradient chemical potential outer layer is composed of multiple layers of oxides with different sodium contents, and the high entropy oxide core is a single-phase solid solution formed by doping multiple transition metal elements in equiatomic ratios.
2. A layered high entropy oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The high entropy oxide core includes Fe, Co, Ni, Sn and Ti, and Fe, Co, Ni, Sn and Ti are doped in an atomic ratio of 1:1:1:1:
1. The grain size of the high entropy oxide core is 100nm to 500nm.
3. The layered high entropy oxide sodium ion battery positive electrode material according to claim 1, characterized in that: Fe, Co, Ni, Sn and Ti are respectively Fe2O3, Co3O4, NiO, MnO2 and TiO2 with a purity of more than 99.9%.
4. The layered high entropy oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The graded chemical potential outer layer is deposited layer by layer by chemical vapor deposition technology, and the thickness of each oxide layer during the coating process is 10-50nm.
5. The layered high entropy oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The thickness of the phase change stress buffer layer is 0.1-5 μm.
6. The layered high entropy oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: Fe2O3, Co3O4, NiO, MnO2 and TiO2 are mixed in an equiatomic ratio to obtain a precursor powder, and then the precursor powder is evenly mixed with anhydrous ethanol to obtain product ①; Step 2: Use a high-energy ball mill to ball mill the product ①, the ball milling conditions are set to 200-400 rpm / min, and the ball milling time is 2-5 hours. After the ball milling is completed, precursor powders of various transition metals are obtained; Step 3: Pre-sintering the precursor powders of various transition metals at a temperature of 700°C for 4 hours, and then sintering at a high temperature of 850°C-950°C for 8-12 hours to form a high entropy oxide core; Step 4: uniformly coating the sodium silicate sol on the surface of the high entropy oxide core, drying the coated material at 70°C, and then calcining it at a temperature range of 300°C-500°C for 1-3h, and forming a phase change stress buffer layer on the surface of the high entropy oxide core after calcination; Step 5: using chemical vapor deposition technology to deposit oxide layers with different sodium contents on the surface of the phase change stress buffer layer to prepare a gradient chemical potential outer layer; Step 6: Grind and sieve the prepared preliminary positive electrode material to obtain a positive electrode material with a particle size of 2-10 μm.
7. A layered high entropy oxide sodium ion battery positive electrode material according to claim 6, characterized in that: The steps of depositing oxide layers with different sodium contents on the surface of the phase change stress buffer layer using chemical vapor deposition technology are as follows: Step 5.1: placing the high entropy oxide core in a CVD reaction chamber, then introducing sodium precursor gas and argon gas into the CVD reaction chamber, reacting at a reaction temperature of 300° C. to 500° C. for 1 to 3 hours; Step 5.2: After all layers are deposited, keep the argon flow, and then anneal at 500 °C for 2 h.
8. The layered high entropy oxide sodium ion battery positive electrode material according to claim 6, characterized in that: In step 1, the mass ratio of the precursor powder to anhydrous ethanol is 1:(2-5).
9. The layered high entropy oxide sodium ion battery positive electrode material according to claim 7, characterized in that: The gradient chemical potential outer layer has an inner layer, an intermediate layer, and an outer layer with a gradually decreasing sodium content from high to low. When depositing the inner layer, the sodium precursor gas concentration is set to 0.5M, the argon gas flow rate is 150sccm, and the deposition time is 1h. When depositing the intermediate layer, the sodium precursor gas concentration is adjusted to 0.2M, the argon gas flow rate is maintained at 150sccm, and the deposition time is 45min. When depositing the outer layer, the sodium precursor gas concentration is adjusted to 0.05M, the argon gas flow rate is 150sccm, and the deposition time is 30min.
10. The layered high entropy oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The chemical formula of the prepared positive electrode material is Na x (Fe y Co y Ni y Mn y Ti y )O2, where 0≤x≤1, 0.1≤y≤0.31.